Exogenous Abscisic Acid Mediates Berry Quality Improvement by Altered Endogenous Plant Hormones Level in “Ruiduhongyu” Grapevine - Li, Jiajia; Liu, Boyang; Li, Xiangyi; Li, Dongmei; Han, Jiayu; Zhang, Ying; Ma, Chao; Xu, Wenping; Wang, Lei; Jiu, Songtao; Zhang, Caixi; Wang, Shiping (Frontiers in Plant Science, 2021)
Abscisic acid (ABA) plays a key role in fruit development and ripening in non-climacteric fruit. A variety of metabolites such as sugars, anthocyanins, fatty acids and several antioxidants, which regulated by various phytohormones, are important component of fruit quality in grape. Here, grape cultivar ‘Ruiduhongyu’ was used to investigate the relationship between endogenous phytohormones and metabolites associated to fruit quality under exogenous ABA treatment. 500 μM ABA significantly improved the appearance parameters and many metabolites content including sugar, anthocyanin, and other compounds. Exogenous ABA also improved the contents of ABA, auxin (IAA) and cytokinins (CTKs) and transcription level of ABA biosynthesis and signaling related-genes in fruit. Furthermore, a series of genes involved in biosynthesis and metabolite pathway of sugars, anthocyanins and fatty acids showed significantly up-regulated under 500 μM ABA treatment. In addition, pearson correlation analysis demonstrated that there are strongly cooperativities in the ABA/kinetin (KT)-appearance parameters, ABA/IAA/KT-sugars, ABA/indolepopionic acid (IPA)/zeatin riboside (ZR)-anthocyanins, and gibberellin 3 (GA3)/methyl jasmonate (MeJA)-fatty acids, which might be the major causal relationship in fruit quality formation. These results laid a primary foundation for better understanding that exogenous ABA improve fruit quality by mediating the endogenous phytohormones level in grape.